Análise experimental comparativa entre uma bomba de calor e uma resistência elétrica como dispositivo de apoio de energia para um aquecedor solar de água - Roberts Vinicius de Melo Reis (2012)
Heating water by means of solar energy can significantly reduce fossil fuel consumption. However, the intermittent lack of sunlight requires an alternative energy source to supplement or substitute for the solar collectors employed for water heating. Generally, this alternative energy is an electrical resistance, whose thermal efficiency is less than 100%,indicating low system efficiency. The aim of this thesis is to perform an experimental analysis of an alternative system to support solar water heating with a better cost-benefit ratio than that of electrical resistance. For this purpose, a heat pump was designed, constructed, andexperimentally tested and then compared with the electrical resistance system. To reduce the installation cost, the heat pump was designed with a low-cost alternative type. To improve the systems performance, a static evaporator (fanless) was used as a substitute for the conventional evaporator alongside the cooling pump refrigeration circuit. The meancoefficient of performance (COP) for the heat pump was 2.15. The moderate cost of the acquisition and installation of the heat pump allows a return on investment between 2.5 and 4.5 years, depending on the city in which the system is used. Considering that the equipment has an estimated lifespan of 15 years, the internal rate of return (IRR) varies from 17.3 to 37.9%, which is attractive for investment.